Understanding the Psychological Report of a Child: What Happens During the Psychological Assessment Process? - Gołuch, Dominik (Social and Personality Development in Childhood, 2025)
A child psychological assessment is a comprehensive process designed to understand and assess a child’s psychological, emotional, cognitive, and behavioural functioning. The aim of this chapter is to present basic information about the typical structure of psychological reports and to present important issues related to the process of diagnosing children and adolescents. This will make it easier to understand how the assessment is carried out and what to focus on when getting acquainted with the report.The chapter discusses basic issues related to the process of psychological assessment of children and adolescents. To better understand what happens during the assessment, the standards that research tools should meet (in terms of objectivity, standardisation, validity, reliability, and normalisation) are discussed briefly. Moreover, various purposes of diagnoses and forms of diagnoses are indicated. Standards for conducting psychological diagnoses are discussed, and typical elements of the diagnostic process are described. It is indicated how children may perceive a psychological assessment situation, and, referring to the transactional model of psychological stress, the most typical factors influencing the perception of the situation are described. The roles of parents, guardians, and the psychologist-diagnostician in the entire process are indicated, along with how they can shape the process to make it more comfortable for the child. General issues related to diagnosing children at various stages of development are also discussed.Keywords: psychological diagnosis; psychometric tools; diagnosis of children and adolescents; fear of evaluation; psychological stress